Survivors’ Paths Toward Forgiveness in Restorative Justice Following Sexual Violence - Hadar, Natalie (Criminal justice and behavior, 2023)
Sexual violence (SV) yields complex justice and therapeutic needs among its survivors. Restorative justice (RJ), conducted in addition to or instead of the criminal justice process following SV, provides a platform to address these needs and repair the harm. This study describes the dynamics of RJ processes following SV, leading to the emergence of dialogic forgiveness. Dialogic forgiveness refers to a reduction in negative thoughts, feelings, and motivations toward the responsible person (RP), and the emergence of positive ones within a process of mutual communication between the survivor, RP, and supporters. Focusing on survivors’ experiences, this study, conducted in Israel, is based on 16 semi-structured in-depth interviews with SV survivors who participated in RJ encounters, their five supporters, and five RJ facilitators. Gestures of accountability, humanization, and gratitude were identified as crucial elements of implicit and explicit dialogic forgiveness, demonstrating the healing power of RJ following SV.